Temperature of cutaneous and subcutaneous tissue during the application of aerosols in rats - Andre de Oliveira Teixeira; Cassio Noronha Martins; Antônio Marcos Vargas da Silva; Alexandro Marques Tozetti; Rodrigo Della Méa Plentz; Luis Ulisses Signori (Universidade Estadual de Maringá, 2014)
This study compared the thermal changes of cutaneous and subcutaneous tissues exposed to different aerosols. Thirty-six adults Wistar rats were arranged in two treatment groups, one exposed to methyl salicylate (GSM; n = 9 skin and n = 9 subcutaneous) and the other exposed to diclofenac diethylammonium (GDD; n = 9 skin and n = 9 subcutaneous) aerosols. Five jets were applied for one-second through an apparatus to reduce spray dispersion (3 cmdiameter) in the lateral left thigh of the animals. Temperatures were measured every minute (min.) during 30 min., with a digital thermometer. In the skin tissue the sensor was positioned manually, in the subcutaneous tissue it was surgically inserted through the rear face and positioned in the lateral thigh. The skin temperature has homogeneously reduced in both groups. In the subcutaneous tissue the GDD has induced hypothermia from the 2nd to 20th min., the lowest temperature was recorded on the 7th min. (-3.6 ± 0.2ºC in relation to basal). Lowering the temperature by GSM took place from the 1st to 21st min, and the lowest temperature occurred on the 1st min (-9.7 ± 0.5ºC in relation to basal). In the three initial minutes the GSM had temperatures 25, 10 and 5% lower than the GDD. Aerosols have induced hypothermia in the tissues, while the GSM has decreased faster and reached lower values of temperature shown in the subcutaneous tissue.